Effect of e-HRM Transformation, HR Quality Development, and Information Technology on Organizational Performance - Halimatussaadah halimatussaadah (Greenation International Journal of Tourism and Management, 2023)
A scientific article from a literature study titled "Transformation of e-HRM in Information Technology-Based HR Quality Development on Organizational Performance" aims to develop a research hypothesis on the impact of variables to be used in additional research, within the context of management information systems. This paper was written using the library research approach, with information from online academic databases like Google Scholar, Mendeley, and others. As a consequence of this article, it has been determined that: 1) e-HRM transformation; 2) HR Quality Development; and 3) Information Technology all have an impact on organizational performance.